2023
DOI: 10.1097/inf.0000000000004037
|View full text |Cite
|
Sign up to set email alerts
|

Virologic Outcomes and ARV Switch Profiles 2 Years After National Rollout of Dolutegravir to Children Less Than 15 Years in Southern Mozambique

Michelle M. Gill,
Nicole Herrera,
Rui Guilaze
et al.

Abstract: Background: Dolutegravir (DTG) was scaled up globally to optimize treatment for children living with HIV. We evaluated the rollout and virological outcomes after DTG introduction in Mozambique. Methods: Data from children 0–14 years with visits from September 2019 to August 2021 were extracted from records in 16 facilities in 12 districts. Among children ever on DTG, we report treatment switches, defined as changes in anchor drug, regardless of changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The study period also coincided with the rollout of new pediatric drug formulations and treatment guidelines, during which time children who had been receiving a 3-month supply were offered a single month only of the new regimen before returning to the 3-month supply after an acceptability assessment. Other analyses of this cohort found that 88% of children aged 5 years and older had at least one regimen switch during the study period [30]. These switches may have contributed to more frequent clinical…”
Section: Discussionmentioning
confidence: 84%
“…The study period also coincided with the rollout of new pediatric drug formulations and treatment guidelines, during which time children who had been receiving a 3-month supply were offered a single month only of the new regimen before returning to the 3-month supply after an acceptability assessment. Other analyses of this cohort found that 88% of children aged 5 years and older had at least one regimen switch during the study period [30]. These switches may have contributed to more frequent clinical…”
Section: Discussionmentioning
confidence: 84%
“…In studies in Kenya and at Baylor sites in Botswana, Eswatini, Lesotho, Malawi, Tanzania, and Uganda [ 23 , 33 ], the authors reported viral suppression rates of 93.4–95.8% when applying a threshold of 1000 copies/ml, where in our study, 96.1% had a viral load less than 1000 copies/ml at 24 months. However, other studies have reported lower viral suppression rates after transition to dolutegravir (Mozambique: 76.2% [ 25 ]; Tanzania: 82.5% [ 34 ]), raising questions about the comparability of HIV programs and its populations in sub-Saharan Africa [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Real-world outcomes among adults appear promising [16–21]. However, observational studies describing paediatric treatment outcomes after the rollout of dolutegravir are currently scarce [18,22–25].…”
Section: Introductionmentioning
confidence: 99%